Caractériser les valeurs environnementales au cours du temps : une étape indispensable à la gestion des patrimoines naturels : Le cas de la restauration des bras morts de l’Ain et du Rhône - Marylise Cottet (VertigO)
An environment is a heritage if it represents a common good, transmitted from one generation to another, due to the values they associate with it. Any heritage implies to leave a legacy. In order to better understand the fabrication of natural heritages, the values which the older generation associates with environments have to be studied. These values influence the choice of the environments deserving to be transmitted. The restoration of fluvial wetlands of the Rhône and Ain Rivers gave an operational frame to this research : an environment can be preserved over a long timeframe only if it is socially meaningful and is perceived as a heritage. 31 interviews were conducted to identify which values are associated with fluvial wetlands according to the older generation. A content analysis – using eight values for the coding – was conducted. The older generation used to practice fluvial wetlands, giving rise to multiple values. Thus, according to her, these environments represent natural heritages. This result shows that natural heritage can be defined spontaneously and do not require institutional protection. It also shows that natural heritages could be challenged by an evolution of social practices. These findings raise many questions for the management of natural heritages.